2020
DOI: 10.1016/j.chemphyslip.2020.104911
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-dependent conformational landscape of the ErbB2 growth factor receptor dimers

Abstract: Altered lipid metabolism has been linked to cancer development and progression. Several roles have been attributed to the increased saturation and length of lipid acyl tails observed in tumors, but its effect on signaling receptors is still emerging. In this work, we have analyzed the lipid dependence of the ErbB2 growth factor receptor dimerization that plays an important role in the pathogenesis of breast cancer. We have performed coarse-grain ensemble molecular dynamics simulations to comprehensively sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…The ordering effect was stronger for membranes with already higher order parameter. This is in agreement with stronger variation of membrane thickness around ErbB2 dimers in DPPC as compared to DLPC bilayers [24]. We speculate that this represents a self-reinforcing mechanism for dimer formation, since the dimerization is more preferable for systems with higher order.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The ordering effect was stronger for membranes with already higher order parameter. This is in agreement with stronger variation of membrane thickness around ErbB2 dimers in DPPC as compared to DLPC bilayers [24]. We speculate that this represents a self-reinforcing mechanism for dimer formation, since the dimerization is more preferable for systems with higher order.…”
Section: Discussionsupporting
confidence: 86%
“…The molecular mechanism for this different behavior still needs to be revealed. The modulation of the structure of dimers by different membrane environments, comprised of only one lipid type, has also been reported for ErbB2 TMDs [24]. Interestingly, we also showed that the free energy of dimerization for POPC-Erg and DOPC systems without PS is slightly lower for LH configurations as compared to RH ones, whereas for DOPC systems with PS the opposite holds.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Several studies also suggested that the lipid environment may control the mode of dimerization. 14,17,23 As a further examination of the convergence of the dimer binding modes, we calculated the free energy of binding for EphA1, Caution needs to be exercised when comparing ab initio predictions, MD simulation results or even structures derived from experiments. First, the comparison needs to be performed for the same TM peptide or protein construct, as well as for the same membrane composition.…”
Section: Resultsmentioning
confidence: 99%